Hematological and Biochemical Reference Intervals in Nepal: A Narrative Review - Lamsal, Swikar; Chaudhary, Roshan Kumar; Mahat, Aayusha; Rimal, Usha; Sah, Surya Dev Kumar; Marasini, Surendra; Joshi, Bishal Raj (Nepal Journal of Health Sciences, 2025)
An accurate interpretation of hematological and biochemical parameters is important for clinical diagnosis and decision making. Hematological parameters, such as hemoglobin, hematocrit, and white blood cell counts, tell about blood health, while biochemical parameters, including liver enzymes, renal markers, lipid profiles, and blood glucose, indicate metabolic and organ function. Reference Intervals (RI), which statistically represent central 95% values of healthy individuals, vary by population due to different factors. This narrative review aims to evaluate the hematological and biochemical reference ranges currently used in major hospitals across Nepal. In this review laboratory reference intervals for regular hematological and biochemical parameters used in 8 different hospitals from Nepal, which are located in Provinces 2, 3 and 4, with internationally accepted standard intervals, taken from recognized international guidelines, including World Health Organization and American Diabetes Association and comparison was done. Laboratory data were collected using a preset proforma designed to systematically record reference ranges from blank report sheets of the respective hospitals. It was found that most of the reference intervals used by these hospitals slightly varied with the internationally accepted standard intervals. However, some parameters like Fasting Blood Sugar, Blood Urea, and CT showed larger variations. Therefore, for accurate diagnosis and treatment of patients in Nepal, such a range of reference intervals shall be used that are based on the country’s population, diet, genetics and environment. It is also essential to update the intervals on a timely basis. This ensures the most effective decisions which doctors can make for a patient’s health.